2014
DOI: 10.4238/2014.january.28.11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new wheat-Aegilops biuncialis addition line conferring quality-associated HMW glutenin subunits

Abstract: ABSTRACT. In this study, a new disomic addition line, 12-5-2, with 44 chromosomes that was derived from BC 3 F 2 descendants of the hybridization between Triticum aestivum cv. CN19 and Aegilops biuncialis was created and reported. 12-5-2 was immune to both powdery mildew and stripe rust and has stable fertility. Fluorescence in situ hybridization and C-banding revealed that 12-5-2 was a 1U b disomic addition line (ADL1U b ). The seed storage protein electrophoresis showed that 12-5-2 presented all high molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
0
21
0
5
Order By: Relevance
“…Addition of alien HMWGS in wheat-Ae. biuncialis addition line also enhanced the SDS Sedimentation value (Zhou et al 2014). The micro-sedimentation test of the PRH derivatives indicated that the addition of 1U specific HMWG subunits increased the MST values only in the presence of Glu-1D as their absence in PRH B-58-3 derivative gave extremely low MST values.…”
Section: Micro Sds Sedimentation and Total Protein Contentmentioning
confidence: 89%
See 1 more Smart Citation
“…Addition of alien HMWGS in wheat-Ae. biuncialis addition line also enhanced the SDS Sedimentation value (Zhou et al 2014). The micro-sedimentation test of the PRH derivatives indicated that the addition of 1U specific HMWG subunits increased the MST values only in the presence of Glu-1D as their absence in PRH B-58-3 derivative gave extremely low MST values.…”
Section: Micro Sds Sedimentation and Total Protein Contentmentioning
confidence: 89%
“…biuncialis addition lines have been used for the transfer of HMW glutenin subunits from Ae. biuncialis to wheat through induced homoeologous pairing (Zhou et al 2014) while wheat-Ae. kotschyi addition lines were used for enhancement of grain protein, Fe and Zn content (Verma et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, plenty of wheat-alien addition lines derived from multiple species of Triticeae have been obtained. These Triticeae species include Hordeum vulgare L. [4–7], Secale cereale L. [8,9], Aegilops speltoides [10,11] and Haynaldia villosa [12,13] and so on. However, most wheat-alien disomic addition lines could not be directly used in wheat breeding due to the presence of linkage drag.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of an alien genetic germplasm is a common method for genetic improvement of wheat. Many wild relatives with important agronomic traits, such as rye (Secale cereale L.), Haynaldia villosa, and Elytrigia elongata, are ideal materials for use in wheat genetic breeding (Qi et al, 2007;Gill et al, 2011;Kang et al, 2011;Liu et al, 2011;Jauhar and Peterson, 2013;Zhou et al, 2014). Rye is a valuable source of resistance, stress tolerance, and high yield genes, and it has been extensively used for yield improvement, disease resistance, and environmental adaptation of common wheat (Friebe et al, 1996;Tang et al, 2009;Ren et al, 2011).…”
Section: Introductionmentioning
confidence: 99%